A framework for user-centric autonomic management - Barraca, João Paulo (2012)
This paper presents a novel autonomic management framework for user-centric networks. The framework assumes users are directly involved, or have direct interest, on their communication system, and as such, place user-related constrains on the behavior of the system. Groups of interest, formed either implicitly or explicitly, by users are considered inside the community concept, which the framework supports. For the realization of this concept, we require a new knowledge and logic layer, which we describe. This framework has been instantiated and tested in a small environment. The results showed the added flexibility of our framework, and its ability to integrated diverse user requirements.